BRD4 promotes heterotopic ossification through upregulation of LncRNA MANCR. Issue 10 (1st October 2021) - Liu, Lei; Li, ZiHao; Chen, Siwen; Cui, Haowen; Li, Xiang; Dai, Guo; Zhong, Fangling; Hao, Wenjun; Zhang, Kuibo; Liu, Hui
Abstract : Aims: Acquired heterotopic ossification (HO) is a debilitating disease characterized by abnormal extraskeletal bone formation within soft-tissues after injury. The exact pathogenesis of HO remains unknown. It was reported that BRD4 may contribute to osteoblastic differentiation. The current study aims to determine the role of BRD4 in the pathogenesis of HO and whether it could be a potential target for HO therapy. Methods: Achilles tendon puncture (ATP) mouse model was performed on ten-week-old male C57BL/6J mice. One week after ATP procedure, the mice were given different treatments (e.g. JQ1, shMancr). Achilles tendon samples were collected five weeks after treatment for RNA-seq and real-time quantitative polymerase chain reaction (RT-qPCR) analysis; the legs were removed for micro-CT imaging and subsequent histology. Human bone marrow mesenchymal stem cells (hBMSCs) were isolated and purified bone marrow collected during surgeries by using density gradient centrifugation. After a series of interventions such as knockdown or overexpressing BRD4, Alizarin red staining, RT-qPCR, and Western Blot (Runx2, alkaline phosphatase (ALP), Osx) were performed on hBMSCs. Results: Overexpression of BRD4 enhanced while inhibition of Brd4 suppressed the osteogenic differentiation of hBMSCs in vitro. Overexpression of Brd4 increased the expression of mitotically associated long non-coding RNA (Mancr). Downregulation of Mancr suppressed the osteoinductive effect of BRD4 . In vivo, inhibition of BRD4 by JQ1 significantly attenuated pathological bone formation in the ATP model (p = 0.001). Conclusion: BRD4 was found to be upregulated in HO and Brd4 -Mancr-Runx2 signalling was involved in the modulation of new bone formation in HO. Cite this article: Bone Joint Res 2021;10(10):668–676.